Pendekatan Tahlili Hadits terhadap Krisis Kemanusiaan di Palestina - Masitha, Sinta; Hairul Hudaya (STAIN MAJENE, 2025)
Abstract The humanitarian crisis in Palestine, ongoing since the Gaza blockade in 2007, constitutes a multidimensional challenge encompassing social, economic, psychological, and humanitarian dimensions. Prolonged armed conflict, structural violence, and limited international intervention have exacerbated civilian suffering, particularly among women and children. Within this context, Islamic teachings, especially Prophetic hadith offer an ethical foundation for social solidarity and humanitarian responsibility. Nevertheless, contemporary applications of hadith in humanitarian discourse often remain normative and literal, lacking contextual analytical depth. This study employs a qualitative methodology using a hermeneutical tahlili approach to hadith analysis. The primary source is the hadith “Al-Muslimu akhu al-Muslim” as recorded in Sahih Muslim, analyzed through sanad authentication, matan examination, and contextual interpretation based on classical and contemporary scholarship. Secondary sources include academic journals, humanitarian reports, and interdisciplinary studies on social solidarity and the Palestinian crisis. The findings demonstrate that the hadith articulates comprehensive ethical imperatives, including the prohibition of oppression, neglect, and humiliation, alongside the obligation of active solidarity. The study concludes that the tahlili hadith approach provides a contextualized ethical paradigm capable of guiding concrete humanitarian engagement and strengthening Islamic social responsibility in responding to the Palestinian humanitarian crisis.